الانتماء النقابي والإضرابات في الجزائر دراسة ميدانية للنقابات المستقلة في قطاع التربية - صوالحية, منير (Sciences de l'Homme et de la Société, 2014)
جاءت هذه الدراسة لتبين طبيعة العلاقة النقابية لأساتذة الثانويات، وموقفهم من المشاركة في الإضرابات التي تدعو إليها النقابات المستقلة في قطاع التربية، استخدمت الاستمارة بعد تحكيمها، وتوزيعها على عينة الدراسة المقدرة بـ (531) أستاذًا من (26) ثانوية في الجزائر، وكان من أهم نتائج الدراسة ما يلي: في الجزائر نجد الكثير من الامتدادات بين السياسي والاجتماعي، ومعظم الأساتذة هم منخرطون لا يضطلعون بأنشطة نقابية. نوعية  المطالب  هي العامل  الرئيسي في تجنيد الأساتذة، ووجود مطلب الأجور على قائمة  اللائحة المطلبية  كافيًا  في رفع  نسبة الانخراط في حين  أن غيابه يقلل منها. Abstract: This study indicated the nature of the relationship of association for teachers of secondary schools, and their position on the participation in the strikes called by independent Syndicates in the education sector. The researcher used a form prepared for this purpose, to be distributed to a sample study estimated (531) teachers from (26) secondary schools in Algeria. The most important results of the study include: A lot of extensions between the political and the social fields in Algeria, Most teachers engaged in Syndicate activities do not fulfill their duties, quality demands that are the main factor in the engagements, and the demand for wages on the list of their demands enough to raise the proportion of engagement while the absence reduces them.